Convergence of regional GDP per capita among the big islands in Indonesia - Murbanto Sinaga; Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Daniel Collyn (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research aims to analyze the regional GDP per capita convergence on the big five islands in Indonesia, which is Sumatera, Java, Borneo, Celebes, and Moluccas and Papua during period 2012-2021. Analyzed convergence included Sigma Convergence, Absolute Beta Convergence, and Conditional Beta Convergence. Data that is used in this research is Panel Data. Data analysis technique is Panel Data Analysis Method with Fixed Effect Model (FEM) approach. Results of the analysis show that the convergence the regional GDP per capita convergence on the big five islands in Indonesia is happened during period 2012-2021, meaning there is an indication that income dispersion between Sumatera, Java, Borneo, Celebes, and Moluccas and Papua is becoming smaller. Next, the results show that the beta absolute and conditional convergence is happened, which indicates that income growth per capita for the underdeveloped islands is higher than the advanced economic development islands, pushing for a convergent economic. Population growth and capital expenditure are variables that significantly affect in accelerating this convergence.